Population-based study of acquired cerebellar ataxia in Al-Kharga district, New Valley, Egypt - Farghaly WMA (Dove Medical Press, 2011)
Wafaa MA Farghaly1, Hamdy N El-Tallawy1, Ghaydaa A Shehata1, Tarek A Rageh1, Nabil Abdel Hakeem2, Noha M Abo-Elfetoh11Department of Neurology and Psychiatry, Assiut University, Assiut, Egypt; 2Al Azhar University, Assiut Branch, EgyptBackground: The aim of this research was to determine the prevalence and etiology of acquired ataxia in Al-Kharga district, New Valley, Egypt.Methods: A population-based study of acquired ataxia was conducted in a defined geographical region with a total population of 62,583. A door-to-door survey was used to identify cases of acquired cerebellar ataxia. Patients with acquired cerebellar ataxia at any age and of both genders were included. Cases of known inherited cerebellar ataxia, acquired neurological disorders with ataxia as a minor feature, or pure acquired sensory ataxia, were excluded.Results: We identified 17 cases of acquired ataxia, of which eight were vascular, six were an ataxic cerebral palsy subtype, and three involved postencephalitic ataxia. The crude prevalence rate for acquired ataxia was 27.16/100,000 (95% confidence interval [CI]: 14.3–40.1). The mean age of the patients at interview was 31.8 (range 4–72) years, with a male to female ratio of 2.1:1. The most frequent presenting complaint was disturbance of gait (90.7%). The majority (92%) were ambulatory, but only 9.3% were independently self-caring.Conclusion: This population-based study provides an insight into acquired cerebellar ataxia within a defined region, and may inform decisions about the rational use of health care resources for patients with acquired cerebellar ataxia. The most common causes of acquired cerebellar ataxia in this region were cerebrovascular injury and cerebral palsy.Keywords: acquired cerebellar ataxia, prevalence, subtypes, Egypt